2020
DOI: 10.1186/s12937-020-00546-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional and socioeconomic variations in dietary patterns in a representative sample of young polish females: a cross-sectional study (GEBaHealth project)

Abstract: Background Associations between dietary patterns (DPs) and socioeconomic correlates among adolescents from emerging economy countries are not fully understood. The study analysed variations in DPs adherence depending on country regions and family socioeconomic status (SES) among Polish females. Methods Data from a representative sample (n = 1107) of Polish females 13–21-year-old was used. Four DPs were previously identified by principal component analysis. Regions were ranked by Gross Domestic Product. A SES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 57 publications
3
35
0
1
Order By: Relevance
“…In our study, height and weight in the GSHSs were self-reported [27]; thus, the prevalence of obesity might be underestimated. Previous studies have shown that SES was negatively associated with fast-food consumption [28,29]. Our detailed logistic-regression analysis revealed that food insecurity, which is usually regarded as a proxy for SES, was positively associated with fast-food consumption ( Table 3).…”
Section: Discussionmentioning
confidence: 58%
“…In our study, height and weight in the GSHSs were self-reported [27]; thus, the prevalence of obesity might be underestimated. Previous studies have shown that SES was negatively associated with fast-food consumption [28,29]. Our detailed logistic-regression analysis revealed that food insecurity, which is usually regarded as a proxy for SES, was positively associated with fast-food consumption ( Table 3).…”
Section: Discussionmentioning
confidence: 58%
“…As a result, it is observed that food products labeled as ‘free from’ any ingredient can be perceived as better for health, in comparison with products with no such information [19]. However, following a restricted diet, based on avoiding some type of products, could result in a deficiency in healthy individuals without health issues, which was indicated as a possible health risk in a national Polish study in a representative cohort of girls and young women [46]. For example, gluten-free processed grain products are often lower in fiber, iron, zinc, and potassium than normal grain products [47].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns (DPs) enable a comprehensive assessment of the habitual diet and are widely used in epidemiological studies [1][2][3][4][5]. Identification of DPs emphasizes the importance of holistic evaluation of the diet as different foods are consumed in complex combinations and their synergistic effect on health should be considered in assessing the diet-disease relationship [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Data-driven DPs are identified using statistical methods, for example: cluster analysis (CA), principal component analysis (PCA), explanatory factor analysis (EFA) [5,7,9,11,13,15,17]. Data-driven DPs can combine healthy and less healthy foods (or dietary characteristics) [2,4,16,18]. Although data-driven DPs may not be as polarised as hypothesis-driven DPs, they can more accurately reflect real eating habits as combinations of food consumed in different groups of the population [10,16].…”
Section: Introductionmentioning
confidence: 99%